2019
DOI: 10.12968/jowc.2019.28.4.246
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of polihexanide use in wound antisepsis in order to clarify ambiguities of two animal studies

Abstract: Objective: Due to classification of the agent polihexanide (PHMB) in category 2 ‘may cause cancer’ by the Committee for Risk Assessment of the European Chemicals Agency in 2011, the users of wound antiseptics may be highly confused. In 2017, this statement was updated, defining PHMB up to 0.1% as a preservative safe in all cosmetic products. In the interest of patient safety, a scientific clarification of the potential carcinogenicity of PHMB is necessary. Methods: A multidisciplinary team (MDT) of microbiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 75 publications
0
19
0
1
Order By: Relevance
“…Nevertheless, the concentration of antimicrobial substances in modern antiseptics used for local treatment of wound and/or skin lesions frequently exceeds a value of 250 mg/L. The most prominent examples are octenidine- and polihexanide-containing antiseptics, of the aforementioned concentrations of antimicrobial substances equal of 1000 mg/L [ 46 , 47 ]. Regardless of the numerous positive features of commercial applied antiseptics for wounds, they nonetheless display specific limitations that peptides do not.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the concentration of antimicrobial substances in modern antiseptics used for local treatment of wound and/or skin lesions frequently exceeds a value of 250 mg/L. The most prominent examples are octenidine- and polihexanide-containing antiseptics, of the aforementioned concentrations of antimicrobial substances equal of 1000 mg/L [ 46 , 47 ]. Regardless of the numerous positive features of commercial applied antiseptics for wounds, they nonetheless display specific limitations that peptides do not.…”
Section: Discussionmentioning
confidence: 99%
“…One such example is the metal organic framework AGMNA, which includes silver (a known antimicrobial agent) and an anti-metabolite, 2-thio-nicotinic acid (H2MNA) [31]. This compound has been investigated as a substitute for the more widely used component polyhexanide, for which there are concerns due to its suspected carcinogenic effects [71]. AGMNA demonstrated higher effectiveness than polyhexanide against S. aureus, despite showing no signs of in vivo or in vitro toxicity [72].…”
Section: Novel Therapeuticsmentioning
confidence: 99%
“…Therefore, alternative substances and decolonization strategies have been evaluated or are currently being used [18,19]. Polyhexanide is a safe antiseptic substance, which is widely used for wound disinfection [20][21][22]. A randomized controlled trial showed no superiority for the decolonization of MRSA carriers when compared to placebo [21].…”
Section: • To Identify and Decolonize S Aureus Carriers Withmentioning
confidence: 99%